Food Redistribution in the Nordic Region : Experiences and results from a pilot study - Hanssen, Ole Jørgen; Ekegren, Per; Gram-Hanssen, Irmelin; Korpela, Pirjo; Langevad-Clifforth, Nanna; Skov-Olsen, Kristin; Silvennoinen, Kirsi; Stare, Malin; Stenmarck, Åsa; Svanes, Erik (Nordic Council of Ministers, 2014)
This report summarizes experiences from Phase I in a Nordic project on food redistribution through food banks and direct redistribution, as well as giving an overview of laws and regulations on the area. The project was initiated by the Nordic Council of Ministers as part of the Nordic Prime Ministers’ green growth iniatiative, The Nordic Region – leading in green growth, with budget from the Food and Agriculture program. The project has focused on redistribution of food that has been donated to prevent food waste, which means that ordinary sponsored food, either free of charge or to a very low price, is not included. The main goals of this study and the report has been to: - Give an overview and evaluation of the extent and potential effects of food redistribution in the Nordic region, both via food banks and more direct and local redistribution. - To summarize the legal basis for regulation and control with food redistribution in the Nordic countries. - To evaluate to what extent it has been harmonized or if it is regarded as important barriers to development of food redistribution. There are few studies and little scientific data on food redistribution in a waste prevention perspective. Some new references to studies in the UK and Australia were found interesting through this study. Food banks are not a well-defined concept in present literature. In this report we have limited the concept of food banks to specific organisations that have been set up to function as open redistribution centres and where several stakeholders collaborate in establishment and operation. Matsentralen in Norway, fødevareBanken in Denmark and Allwin in Sweden fits within this definition, with a question mark on how the stakeholders are involved in the operation of Allwin. Redistribution of food has been divided into two main approaches: - Redistribution from food supply chain donors via redistribution centres like food banks, for storage and further distribution to end users which typically are charity organisations (the typical “food bank redistribution route”). - Direct redistribution from food supply chain donors to charity organisations, which is typical for local redistribution. Another important part of the project has been to compile available information about laws and regulations in the Nordic countries that can be potential barriers to establishment and operation of food banks and food redistribution in general. The main methodology applied in the second part of the project has been to carry out surveys by questionnaires to key persons in the involved organisations, both in national food banks, national charity organisations, local charity organisations and food donators, in many cases followed up by interviews either by telephone or through physical meetings. The report gives an overview of both food legislation in the EU as well as nationally. Within the European Union food legislation is harmonized. Since 2002 the Union has a general food law; Regulation (EC) No. 178/2002 laying down the general principles and requirements of food law, establishing the European Food Safety Authority and laying down procedures in matters of food safety (hereafter regulation (EC) No. 178/2002). The regulation constitutes the basis for the union food legislation and shall apply to all stages of production, processing and distribution of food and feed. It shall not apply to primary production for private domestic use or to the domestic preparation, handling or storage of food for private domestic consumption. Food banks should be regarded as food business operators according to regulations, and should thus follow the same overall rules as other types of businesses in the food supply chain. However, the four Nordic countries included in this study have defined food banks different with regard to the role in the supply chain, which can give quite different situations with regard to what is accepted and what is not to be redistributed. As far as possible the role of food banks could be harmonised in the Nordic countries. Direct food redistribution is in many cases not specifically mentioned in the survey of regulatory measures, making it unclear how national regulations and rules relates to charity organisations getting food directly from the food supply chain. This should be clarified and harmonised as far as possible. The three food banks that exist in the Nordic region have quite different backgrounds and also quite different models for organisation and ownership. The founding process of the three food banks was also quite different. The Danish and Swedish food banks have been established and developed in a continuous process, whereas the Norwegian food bank was established after two years with planning. The three food banks have also developed quite different business models, where the Swedish one is a private limited company, the Danish one a membership organisations with more than 300 members and the Norwegian one a cooperative organisations mostly owned by the national charity organisations, but also with a number of members. All three food banks were established with a two-sided purpose, both to reduce food waste and to make it easier for charity organisations to get access to food donations. The three food banks do also differ with regard to number of employees and volunteers, which is quite natural taken the length of operation into consideration. The three food banks redistributed in 2013 about 900 tonnes of food, that otherwise would have ended as food waste. The number of meals served based in redistributed food has been estimated to about 1.67 mill in 2013, with about 926,000 in Copenhagen, 346,000 in Oslo and 400,000 in Gothenburg. The most important donors to the food banks today are food producing companies and to some extent wholesale companies, and mainly from the surrounding area of the cities where the food banks are located. In general, there have not been problems with the quality of food being donated, as the regulations on this are the same as for normal food distribution. The problem is more to receive fairly stable amounts of food and to have a sufficient variety of food types. The food banks do both have capacity to receive more food and there is a need for more food for redistribution, so there is potential for increase in redistribution in the future. The main lessons learned from this brief overview of food banks in Nordic countries are that they are a small, but important actor in food waste prevention. It is important to consider the role for food security for low-income people, which gives redistribution a double role in the society. Food banks must find their role between the food sector and charity organisations, to supplement and not compete with the existing systems for redistribution locally. The food banks could also take the roles as “system operators” for redistribution of donated foods and be national competence centres for all actors being involved in food redistribution. Food banks can also have roles in certification of actors being involved in redistribution of food, which should be further discussed in Phase II of the project. The food banks struggle with low incomes and low support from national authorities; it is thus important to consider how the food banks should be financed. National surveys were carried out based in a common research approach and with the same questionnaires applied in all countries. As this survey is the first attempt to get an overview of direct food redistribution in any Nordic country, it should be regarded as a pilot study where the objectives were both to establish a methodology for the survey as well as getting a first overview of the extent of food redistribution outside the “official” food banks. 2–4 cities/regions were included in each country, where the cases were selected in collaboration with national charity organisations. The survey indicated that locally organised direct redistribution makes a significant contribution to prevention of food waste and to social security for low income people in all countries. This does not mean that it will contribute to a big reduction in total amounts of food waste in each country, nor that a large proportion of low-income people will be served with redistributed food. For the weaker groups, this is the most important service of the charity organisations, and donated food makes up more than 50% of served food in most organisations. The figures are still quite uncertain and the regions studied are not representative for the whole country. Finland seems however to have a much better organized and a much higher number of serving places for low income people than the other countries. Food redistribution has a long tradition in most countries, but is still relatively loosely organised by local relationships and direct contacts between persons in the charity organisations and food companies/retail companies. Central agreements between organisations and food and retail companies would certainly have made it easier to establish and manage local and direct redistribution. A main barrier mentioned by the local organisations is lack of resources to establish and maintain a system for receiving food donations. One way to better facilitate food redistribution from food producers and retailers to local charity organisations is by providing access to monetary and human resources for the purpose of establishing and maintaining local systems for receiving food donations. This system also needs to include infrastructure such as storage and cooling facilities as well as solutions for transportation of food from the donor to the organisation. The main findings from direct redistribution of food in the Nordic countries, based in the regional studies carried out shows that the average number of meals served per year per 1,000 inhabitants varies between 217 and 335, whereas the number of food bags delivered per 1,000 inhabitants varies between 17 in Sweden and 522 in Finland. Those figures should be used carefully, since the calculations are based in a number of uncertain conditions which are discussed in the report. Our pilot survey of direct redistribution indicates that direct redistribution today have a much larger volume than the amount of food being redistributed via food banks alone. The study also indicates that it can be a great potential for increasing the amount of food being redistributed in the Nordic countries from the present status, and most of the charity organisations say there is a need for more food donations. Better organisation and clear guidelines from food authorities nationally can make it more acceptable for the food industry and retail companies to donate food, and realise the big potential for redistribution. This survey has shown that there are significant differences in how food redistribution activities are organised in the Nordic countries, and that there are many models for how it can be organised. Food redistribution lack a systems organisation in the Nordic countries and there could be developed a good model that integrate the food banks operating on national and regional levels with local direct redistribution initiatives. There are several areas that are important to be followed up through more specific studies, either as a direct following up from this pilot study or eventually in other similar settings, in the Nordic region or on a European scale. The three areas that have been described and that are proposed as input to discussions for Phase II of the Nordic Food Waste project are: - Following-up study on the quantification of food redistribution in the Nordic region, both via food banks nationally and regionally and direct redistribution locally. - Development of food banks as “system operators” in food redistribution, with regional networks and good collaboration with local direct redistribution systems. - Further development of rules and control routines for both redistribution via food banks and especially for directly to charity organisations within the given EU regulations. This report is part of the Nordic Prime Ministers’ overall green growth initiative: “The Nordic Region – leading in green growth”. Read more in the web magazine “Green Growth the Nordic Way” at www.nordicway.org or at www.norden.org/greengrowth
ISBN 978-92-893-3855-4 (EPUB)